Performance enhancement of a solar air heater using rectangular perforated duct inserts. (1st September 2022) - Arunkumar, H.S.; Kumar, Shiva; Vasudeva Karanth, K.
Graphical abstract: Highlights: Numerical analysis of a double pass SAH with perforated absorber duct inserts. Effect of duct height, hole diameter, and the number of holes are investigated. Two-rows with hole size 5 mm, height ratio 0.67 shows highest performance. Abstract: In the present work, a rectangular aluminium absorber duct with perforations on the upper surface is placed inside the glazed solar air heater duct. Numerical analysis is carried out to study its influence on thermo-hydraulic performance. The absorber duct insert absorbs the radiation heat by inducing turbulence across the flow path due to the presence of perforations. The upper and lower passages are varied in terms of height ratio so as to create a pressure differential between them which generates a crossflow phenomenon. The perforation hole diameter and number of rows of holes are varied, and the flow physics is analysed. Results indicated that perforated configuration showed significantly higher thermo hydraulic efficiency than the plain configuration. A duct height ratio of 0.667, two row configuration with a hole diameter of 5 mm showed maximum performance with the values of thermal and thermo-hydraulic efficiency being 83.01% and 87.06% respectively.